Sport engagement model in Malaysia: Effect of cost and volunteerism - Nor Eeza Zainal Abidin; Hutkemri Zulnaidi; Shariffah Mamat; Nofouz Mafarja (Heliyon, 2023)
Sport engagement plays a crucial role in promoting physical well-being, fostering social connections, and enhancing overall quality of life. However, various factors, including financial constraints and limited resources, can serve as barriers to sport participation. Additionally, volunteerism has been recognized as a significant contributor to the growth and development of sports in communities. This research study aims to explore the relationship between the cost of sport engagement and volunteerism among individuals in Malaysia. This study was conducted to test the effect of sponsorship, expenditure and volunteering on activeness. A causal correlation study was conducted comprising a total of 501 young people in Malaysia who were selected randomly. This study found that sponsorship, expenditure and volunteerism towards activeness amongst youth are at a moderate level. The findings also showed that sponsorship (β = 0.035, sig = 0.682, p > 0.05) and voluntary (β = 0.098, sig = 0.192, p > 0.05) have no significant contribution towards activeness, the sponsorship and volunteering are not factors which contribute to changes in activeness. However, there is a significant effect of expenditure as an intermediary in the relationship between sponsorship and activeness (β = 0.107, sig = 0.001, p < 0.05), whilst there is no significant effect of expenditure as a mediator in the relationship between voluntary and activeness (β = 0.022, sig = 0.115 p > 0.05). This study provides implications to Ministry of Youth and Sports that sponsorship, expenditure, and voluntary are not main factors which contribute to activeness.